Implementing Feminist Language Pedagogy: Development of Students' Critical Consciousness and L2 Writing - Hayley Anne Cannizzo (MDPI AG, 2021)
Feminist pedagogy is a teaching practice, philosophy and process that seeks to confront and deconstruct oppressive power structures both within and outside of the classroom using a gendered lens. As Women's Studies departments continue to grow in many universities, feminist pedagogy seems to be gaining popularity as an approach to engaging students in liberatory classroom practices. However, feminist language pedagogy (feminist pedagogy in the second language learning context) appears to have stagnated. This paper investigates the implementation of feminist language pedagogy in an EAP writing classroom for first-year students at a public university in the Southwest of the United States. Using action research, the teacher, who is the author of this paper, examined how feminist language pedagogy aids the development of her students' critical consciousness and serves as a motivational tool for L2 writing development. The author finds that even in a short, sixteen-week semester, it is possible for students to foster critical consciousness without sacrificing linguistic development.